Myeloid targeting antibodies PY159 and PY314 for platinum-resistant ovarian cancer - Afshin Dowlati; Judy Wang; Siqing Fu; Amita Patnaik; Minal Barve; Shivaani Kummar; Abdul Rafeh Naqash; Patricia LoRusso; Michael Gordon; Debra L Richardson; Ira Winer; Christos Kyriakopoulos; et al. (Journal for ImmunoTherapy of Cancer)
Background Novel treatment options are required in patients with platinum-resistant ovarian cancer (PROC). Myeloid-derived suppressor cells promote a hostile tumor microenvironment and are associated with worse clinical outcomes in PROC. We evaluated the safety and preliminary efficacy of PY159, an agonist antibody to Triggering receptor expressed on myeloid cells-1 (TREM1) that reprograms immunosuppressive intratumoral myeloid cells, and PY314, an antagonist antibody to Triggering receptor expressed on myeloid cells-2 (TREM2) that depletes tumor-associated macrophages, as single agents and in combination with pembrolizumab in subjects with PROC.Methods PY159 and PY314 were individually evaluated in patients with PROC. Patients were treated with monotherapy (PY159 3 mg/kg or PY314 10 mg/kg), based on the recommended dose for expansion derived from the phase 1a studies. At the time of first progression, patients could continue study drug and crossover to combination therapy with pembrolizumab (200 mg) every 3 weeks at the discretion of the investigator. Disease assessment by Response Evaluation Criteria in Solid Tumor version 1.1 was performed every 6 weeks.Results 17 patients were enrolled in the PY159 study (median age 67, range 22–77; median prior therapies 6, range 2–18) and 16 patients in PY314 (median age 65.5, range 49–81; median prior therapies 4, range 2–10). 7 patients in PY159 and 8 patients in PY314 crossed over to combination therapy. Safety events included the following: treatment-related adverse events occurred in 15 patients (88.2%) in PY159 and 9 patients (56.3%) in PY314. Infusion-related reactions occurred in 6 patients (35.3%) in PY159 and 3 patients (18.8%) in PY314. Immune-related adverse events occurred in 13 patients (76.5%) in PY159 (arthralgias) and 1 patient (6.3%) in PY314 (diarrhea). Serious adverse events occurred in 6 patients (36.3%) in PY159 (1 related) and 12 patients (75%) in PY314 (all unrelated). The best radiographic response in PY159 was stable disease in 8/16 patients (50%; median 16 weeks, range 9–33), and in PY314, it was stable disease in 8/16 patients (50%; median 12 weeks, range 6–36). Median PFS was 2.76 months and 2.69 months in PY159 and PY314, respectively. There were no responses in the crossover arm.Conclusions Both PY159 and PY314 were well tolerated, with an acceptable safety profile, as both single agents and in combination with pembrolizumab. Both agents warrant further investigation in heavily pretreated PROC.